Influence of racing position on cycling patterns - Emanuele, U.; Horn, T.; Denoth, J. (ISBS - Conference Proceedings Archive (Konstanz), 2011)
The aim of this study was to examine the effect of racing position on the pedal forces, the kinematics of the lower limbs, the muscular joint moments and the muscular joint powers. Cycling in an upright position (UP) and in a dropped position (DP) was analyzed in six subjects during cycling at 200 W with a cadence of 80 rpm. The pedal forces showed only slight differences between the two positions. The kinematic analyses revealed that only the mean hip angle was affected by body position. The inverse dynamics showed that body position significantly influenced the joint powers. The main reason for these changed power outputs could be the change in mean sarcomere length and mean moment arm of the hip muscles with different racing positions.